Put your best face forward: adolescent use of Facebook and the establishment of a hypermeality - Taddonio, Elizabeth A., author; Diffrient, David Scott, 1972-, advisor; Lupo, Jonathan, committee member; Snodgrass, Jeffrey G., committee member (Colorado State University. Libraries, 2010)
This thesis seeks to understand how adolescents, aged 13-15, use the online social network (OSN) of Facebook to perform identity. Over the course of three chapters, the researcher uses the frameworks of social semiotics, narrative studies, and performance studies to analyze the site's design, features, and users, respectively. This analysis is meant to clarify whether Facebook as a medium rearranges and changes the activities of a generalized adolescent population in U.S. America, or if the medium simply reinforces pre-existing social practices. To answer this question, the study focuses heavily on the use of a new term, "hypermeality," in order to explain the communal narrativization of the social self online. The study concludes by stating that Facebook creates a hyperreal environment for both negative and positive outcomes of networking. These negatives include cyberbullying, self-centrism and problematic Internet use, while the positives include online community building and cosmopolitanism that might extend to offline behaviors and awareness. It is the goal of this thesis to add to the conversation on new media technologies, contributing to a better understanding of how the previously mentioned theoretical frameworks can be applied to the study of OSNs—their role and function in the lives of adolescent computer users. This knowledge should foster the development of safe OSNs, intergenerational computer-mediated communication, and the de-stigmatization of new media cultures.
Department Head: Sue Pendell.